Implementation of Mathematics Learning Through Hydroponic Farming to Improve Mathematics Ability in Early Childhood - Putri, Ni Wayan Suardiati; Wardika, I Wayan Gede; Kencana, Agung Pasek Surya (Universitas Muhammadiyah Mataram, 2022)
This study aims to produce and determine the feasibility of early mathematics learning media through hydroponic farming for Early Childhood. The type of research carried out is development research, because in this study an initial mathematics learning media was developed through hydroponic farming for Early Childhood. The research instruments used were media validation sheets and teacher response questionnaires. The data analysis used is descriptive quantitative. The product produced in this study is a medium for early mathematics learning through hydroponic farming for Early Childhood that meets valid and practical criteria. This study took subjects in Early Childhood at Kartika Kindergarten, Peguyangan Kaja Village. The results of this study regarding media validation showed that the initial mathematics learning media through hydroponic farming for Early Childhood had met the valid criteria. Judging from the results of the analysis of the teacher's response to learning media, namely the teacher's response to the use of media, it shows 75.8% in the good category. This shows that the media can be implemented practically by the teacher.